Studiile de impact - instrumente pentru o mai bună reglementare a politicilor publice în Uniunea Europeană - Gabriela Drăgan; Agnes Nicolescu (European Institute of Romania, 2009)
– This paper analyses the justifications and stages of the elaboration of impact studies at the European level, focusing on the various working methods, be it 'impact matrix' or the 'logic of intervention', which may be adopted by law-makers, in order to improve the regulation mechanisms in the public administration field and shape up new ways in which they could be used. Attention is paid to the role and the utility of impact assessment in elaborating public policies, as well as to the importance of properly using analysis instruments, with a focus on the obstacles and risks associated to the impact assessment process, by comparing different approaches and working methods, from the European and OECD area. Various evaluation patterns from OECD and the EU are presented, with their peculiarities and challenges involved by their implementation, leading to the conclusion that the European assessment pattern is still far away from providing a universal impact analysis model due to the lack of efficient sanctioning mechanisms. The credibility of an impact assessment largely depends on its results, which means they need to be based on correct and updated information, which is at the same time transparent and easy to access and understand. The role of impact assessment and, by extension, of impact studies is to allow lawmakers to check up whether the implementation of existing regulations observes the established indicators, as well as whether the policy in question had reached its objective.
Keywords: 330; Wirkungsanalyse; Politik; Politische Entscheidung; Politische Willensbildung; EU-Staaten